La incidencia de los juegos matemáticos en el desarrollo del pensamiento lógico de los estudiantes del séptimo año de educación general básica de la escuela Manuel Salcedo de la parroquia Eloy Alfaro, cantòn Latacunga - Tutillo Tutillo, Katherin Noemí (2015)
Actually the educative process will be affected for the low academic profit in the kids from different areas to the knowledge it´s for that purpose the present investigation has the main objective to determine the incident of the math games for developing the logic thinking into the learning process. Because the teachers must be training in the math area to guide the student with the principal goal that will be reflexive and critic. For that reason it´s necessary to create and implement a didactic guide of math games that has the same updated educative requirements….